(untitled) (Journal of the College of Basic Education, 2022)
The narrator benefited from the multiplicity of characters and worked to diversify them in all his novels, and the place had a great impact on the character, as the place is affected and influential at the same time. As the place narrows and widens according to the narrator’s point of view. The narrator worked on employing the woman’s personality in multiple roles, but the woman’s role in the war novels was a secondary role that being influenced by the place, and the woman’s personality belongs in Al-Ubaidi’s novels to the attractive character even though it appeared in different roles ((Jeddah, female doctor, secretary, pet, sister) ). Most of the roles of women were not taken a wide area from the novels of Abdul Karim Al-Obeidi, as the mention of women was limited to performing the reflective role of the effects resulting from the events of the war on the place. The narrator worked on finding the visual equivalent in creating his characters. He created a kind of paradox in the combination of the intellectual personality and the personality Amartly. The narrator worked on a statement more than a sign to show the role of the intellectual. Sometimes he is exposed to influences that in turn end up to nothing and at other times he works on a significant cultural change